Effect of Nedocromil Sodium on Aspecific Bronchial Hyper-Reactivity in Asthmatic Children - A. Fiocchi; P. Signoroni; P. Bruni; M. Galeone; E. DeCet; S. Bogacki (Mediators of Inflammation)
The purpose of this study was to evaluate whether nedocromil sodium benefits urban asthmatic children showing seasonal bronchial hyper-reactivity to ultrasonic nebulization of distilled water (UNDW). A prospective, randomized, placebo-controlled, parallel-group, double-blind study was carried out at the outpatient pulmonology service at a tertiary-care teaching hospital. Twelve children living in Milan, who were 7–17 years of age, who were SPT and RAST-negative to perennial allergens, who were suffering from episodic asthma, and showing seasonal bronchial hyper-reactivity to UNDW during winter, participated in this study. All the children received either placebo or nedocromil sodium, 4 mg every 6 h for 6 weeks. Spirometry and UNDW challenge were done at the following times: day−7; day 0; day 1; day 7; day 14; day 28; day 42. No differences were found in the basal spirometric parameters, which were normal in both nedocromil and placebo groups. Bronchial reactivity to UNDW was found to be significantly decreased in the group treated with nedocromtl starting from day 7. It is therefore concluded that nedocromil sodium can reverse bronchial hyper-reactivity caused by seasonal factors such as cold, viral infections and atmospheric pollutants in children suffering from asthma.